2021
DOI: 10.1186/s12910-021-00576-9
|View full text |Cite
|
Sign up to set email alerts
|

Health data research on sudden cardiac arrest: perspectives of survivors and their next-of-kin

Abstract: Background Consent for data research in acute and critical care is complex as patients become at least temporarily incapacitated or die. Existing guidelines and regulations in the European Union are of limited help and there is a lack of literature about the use of data from this vulnerable group. To aid the creation of a patient-centred framework for responsible data research in the acute setting, we explored views of patients and next-of-kin about the collection, storage, sharing and use of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Patients discuss wanting to know their results out of personal curiosity [ 48 ] or peace of mind [ 89 ], because it may provide personal health benefit [ 48 ], clinical utility [ 89 ] or actionability [ 42 , 52 ], or to inform their children of their risks [ 89 ]. A qualitative study of 25 parents highlighted that participants considered ‘actionability’ as a broad concept, encompassing aspects such as medical interventions, lifestyle modifications, education, mental preparation, and planning, including insurance, housing, and finances [ 42 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…Patients discuss wanting to know their results out of personal curiosity [ 48 ] or peace of mind [ 89 ], because it may provide personal health benefit [ 48 ], clinical utility [ 89 ] or actionability [ 42 , 52 ], or to inform their children of their risks [ 89 ]. A qualitative study of 25 parents highlighted that participants considered ‘actionability’ as a broad concept, encompassing aspects such as medical interventions, lifestyle modifications, education, mental preparation, and planning, including insurance, housing, and finances [ 42 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…Posthumous data research gives patients the opportunity to reciprocate: some authors have advocated a human right to participate in science (Vayena & Tasioulas, 2015). In our own empirical research, survivors of sudden cardiac arrest stated that "when you are dead, you are dead, but it would be nice if you can prevent other people from dying in the same way" (Bak et al, 2021). Nonetheless, research with the Acknowledgements The authors wish to thank professor Luciano Floridi for his valuable feedback throughout the writing process and on versions of the paper.…”
Section: Conceptualising Post-mortem Privacy In Health Data Researchmentioning
confidence: 99%
“…The public was similarly divided in another study where 52% supported GE (Global Alliance, 2017). In our own interviews with sudden cardiac arrest survivors, socio-economic data was regarded as more personal than DNA (Bak et al, 2021). Just like DNA sequences, 12 Embodiment is a complex term.…”
Section: Embodimentmentioning
confidence: 99%
“…Similarly, several ESCAPE-NET researchers have told us that they believe "the trust in the researcher should be enough" for people to decide to contribute data. In a study where we interviewed SCA patients who contributed to ESCAPE-NET, we found that trust was indeed one of the key factors for people when deciding to share their personal data for research (Bak et al, 2021). This trust mainly stemmed from their positive experiences with clinicians and with the medical institution conducting the research.…”
Section: Trust As Multi-agent Conceptmentioning
confidence: 99%